Role of R loops in recA-independent homologous recombination of bacteriophage lambda. - Matsumoto, T (1983)
We have previously shown that the DNA-dependent RNA polymerase of Escherichia coli can promote homologous recombination of bacteriophage lambda independently of the recA function. To detect this recombination, we jointly infected the cells with a pair of lambda phages in the presence of chloramphenicol, extracted intracellular lambda DNA molecules, packaged them in vitro, and measured the number of resulting recombinant phage particles. We showed that the recombination of DNA molecules takes place in vitro after extraction of DNA from the cells. We fractionated recombinogenic forms of intracellular lambda DNA and showed that they carry RNA. These and other results suggest that the R (RNA) loop structures, generated by transcription within the cells, promote homologous recombination in vitro. We discuss possible mechanisms of this recombination and compare those with the other forms of general recombination.